Business Analysis of Hand Line Fishing Technique in Pariaman City West Sumatera Province of Indonesia - Gusmawati, Nelva; Amrifo, Viktor; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in May 2016 in the city of Pariaman, West SumatraProvince of Indonesia. The purpose of this research are to analyze the business investment ofhandline fishing gear, profitability of fishing gear extended and the feasibility of catching upwith fishing gear stretching. This research used survey method. The population of theresearch are the owners of handline totaled 129 people, with a total sample of 5 people forfishermen strata 1 and 5 people for fishermen strata 2.The research results businesses overextend profitable fishing gear according to thegross income of handline fishermen fishing strata 1 per year as much as IDR.67.162.000 andfishermen gross income stratum 2 per year as much as IDR.94.630.000,- net income ofhandline fishermen fishing strata 1 per year as much as IDR.18.579.083,3 and net income ofhandline fishermen fishing strata 2 per year as much as IDR.18.695.716,7. Feasibilityanalysis shows the business can be continued according to the value of RCR > 1, the value ofPPC shows long payback of fishermen strata 1 for one year less one day and fishermenstratum 2 for 1 year 1 month 6 days andthen FRR value handline fishermen fishing effortstratum 1 and stratum 2 < bank lending rates prevailing then that business investment shouldbe deposited to the bank because it is more profitable.Keywords: Business Analysis, Handline Fishing, Feasibility Study, Fishermen,Pariaman City